La posición del Tribunal Constitucional español relativa a la posible contradicción entre el Derecho constitucional interno y el Derecho europeo - Sarrión, Joaquín (2023)
We intend to study the Spanish Constitutional Court’s point of view on the possible contradiction between the law of Spain an d that of the European Union. This a legitimate concern, because the European Union’s Court of Justice quickly established the primacy of European Union law over the national law of Member States. The position of the Spanish Constitutional Cour t is complex, given the doubts it has expressed, even showing some hesitation with regard to its understanding of itself as a European judge. From the different perspectives of the German and the Spanish constitutional courts, one can derive some kind of relationship in Europe’s judicial architecture that is dialectical and balan ced, especially in a European Union where political power resides in a system of balances in which forces pull in different directions.